Growth response of Taro (Colocasia esculenta L.) in soil polluted with Abura petroleum oil - JF Bamidele; S Esan (Journal of Applied Sciences and Environmental Management)
Field experiment was conducted to evaluate the effect of crude petroleum oil on cocoyam (Colocasia esculenta L.). Plants were grown in substrates exposed to 0, 1, 2 and 3 L/m2 of Abura crude petroleum oil. There was significant growth stimulation (p 0.05) in terms of number of leaves, petiole length, leaf area, plant dry weight, and chlorophyll content in plants subjected to 1-2 L/m2 oil. The dry biomass as well as other plant growth attributes showed significant reductions in plants grown in soil polluted with 3 L/m2 oil. The highest applied oil dosage also adversely affected the leaf chlorophyll content. The experiment demonstrated that cocoyam is sensitive to crude petroleum oil pollution. @JASEM